Collision metastasis from prostate adenocarcinoma and pancreatic ductal adenocarcinoma to a lung nodule. Issue 3 (March 2023) - Mohamed, Ahmed; Yao, Mark; Saw, Sonia; Clark, Amanda; Madaan, Sanjeev
Introduction: Prostate cancer and pancreatic cancer are often complex pathologies that affect millions of patients worldwide. However, the incidence of a distant collision metastasis of both malignancies remains a rare and often poorly documented incidence. Case presentation: A 75-year-old male patient with past history of prostate cancer on maximal androgen blockade was recently diagnosed with pancreatic cancer for which he underwent radical surgical resection of pancreas with curative intent. A metastatic lung nodule was noted on surveillance CT imaging and, subsequently, biopsied. A diagnosis of collision metastasis from two distinct primary malignancies was histopathologically confirmed following immunohistochemical evaluation. Conclusion: We report the first case of collision metastasis of prostate and pancreatic adenocarcinomata to a lung nodule to the best of our knowledge.